Harnessing your Transferable Skills in a COVID-19 Economy - Khamala, Maya (2021)

Job Search Mentorship During COVID-19 - Khamala, Maya (2021)

Skill-Building & Networking in the Time of COVID-19 - Khamala, Maya (2021)

Annual Report 2020-2021 - Youth Employment Services (YES) (2021)
As a not-for-profit organization, YES enriches the community by providing English-language support services to help Quebecers find employment and start and grow businesses. YES Employment + Entrepreneurship has been broadening access to opportunities for Quebec’s English-speaking community for over 25 years now. As we reflect on the organization’s 25th anniversary in the midst of the pandemic, we are reminded of the vital importance of our career and business support services.

Fall Program Book : September - December 2021 - Youth Employment Services (YES) (2021)

Showing up When it Counts : 2021 Annual Report - Youth Employment Services (YES) (2021)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2021)